Legal Protection of Employees of PT Askes Which Was Transfered By Legal Relationship Becoming Health BPJS Employees - Muhammad Habibi (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2018)
The background of this research is the existence of a legal vacuum due to not regulating the transfer of legal relations of employees. PT ASKES (Persero) becomes an employee of BPJS Kesehatan (a public legal entity) in Law Number 24 of 2011 concerning the Social Security Organizing Body and its implementing regulations and the absence of provisions. which regulates public legal entities. This study uses normative juridical research with the method of legislation approach and grammatical interpretation techniques and systematic interpretation to analyze primary, secondary and tertiary legal materials. The results showed that the legal relationship born after the employees of PT ASKES became employees of BPJS Kesehatan was an employment relationship according to Law Number 13 of 2003 concerning Manpower so that its legal protection other than through work agreements and directors' regulations was also through Law Number 13 of 2003 concerning Manpower Law Number 24 of 2011 concerning the Social Security Organizing Body.